SPE Eastern Regional Meeting 2009
DOI: 10.2118/125903-ms
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal Wells with Multi-Stage Fracs Prove to be Best Economic Completion for Many Low-Perm Reservoirs

Abstract: Like any other business, return on investment (ROI) drives the decision-making processes in the oilfield. The "cut-cost" approach can only be successful when resulting production is adequate. Especially during the past few years, it has been observed that most North America operators using horizontal completions in low-perm oil or gas reservoirs have abandoned the "lowest-cost" approach in favor of a "maximize-production" mindset. Maximizing ROI requires operators to continually evaluate both cost and effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Horizontal wells completed with OHMS have proven to be an excellent economic means to develop low permeability reservoirs 11 . Once the completion assembly is run to the total depth and packers properly placed as per design, the rig can move off location.…”
Section: Discussionmentioning
confidence: 99%
“…Horizontal wells completed with OHMS have proven to be an excellent economic means to develop low permeability reservoirs 11 . Once the completion assembly is run to the total depth and packers properly placed as per design, the rig can move off location.…”
Section: Discussionmentioning
confidence: 99%
“…In a study performed by McDaniel and Rispler (2009), the sand-plug method was the lowest-cost and most efficient method of treating the horizontal-gas wellbores. In many gas plays, operators are successfully using CT-deployed methods to treat multiple intervals.…”
Section: Previous Methodsmentioning
confidence: 99%
“…Field hydraulic fracturing construction data, rock physics logging, and radioactive tracer logging data were used to simulate most of the hydraulic fracturing engineering 23,24 . In response to the issue of the impact of bending stress caused by large inclination and irregular wellbore trajectory on casing strength, Paslay and Cernocky 25 found that bending stress has a significant impact on casing strength under conditions of high dogleg angle and long horizontal sections with irregular wellbore trajectory during on‐site construction operations, and should be considered in casing strength design 26 . Wang pointed out that local bending, squeezing, and shear failure are the main forms of casing failure 27 .…”
Section: Introductionmentioning
confidence: 99%
“…23,24 In response to the issue of the impact of bending stress caused by large inclination and irregular wellbore trajectory on casing strength, Paslay and Cernocky 25 found that bending stress has a significant impact on casing strength under conditions of high dogleg angle and long horizontal sections with irregular wellbore trajectory during on-site construction operations, and should be considered in casing strength design. 26 Wang pointed out that local bending, squeezing, and shear failure are the main forms of casing failure. 27 Yan et al 2 pointed out that during the high-volume fracturing process, the temperature in the wellbore drops rapidly, causing the volume of the confined liquid in the cement sheath voids to shrink, resulting in a decrease in pressure in the cement sheath voids.…”
Section: Introductionmentioning
confidence: 99%